NOAA/NASA Pathfinder climate data - Hayes, Patrick J. (National Geophysical Data center, 1998)
Contains 7 data sets from NOAA/NASA Pathfinder Program. The major portion of the data is of one- by one-degree gridded files with many parameters, most of which are climate-related and can be used for analysis and research. [Disc includes GeoVu Data Browse display program and various data conversion and export programs.].